Antibody response to BNT162b2 mRNA vaccine in gingival crevicular fluid. Issue 1 (11th November 2022) - Han, Pingping; Moran, Corey S.; Sulugodu Ramachandra, Srinivas; Walsh, Laurence J.; Ivanovski, Sašo
Abstract: Background: This prospective cohort study aimed to evaluate the antibody responses in non‐invasive gingival crevicular fluid (GCF) and unstimulated whole saliva to the SARS‐CoV‐2 Spike unit 1 receptor‐binding domain (S1‐RBD) protein following administration of the mRNA BNT162b2 vaccine. Methods: This longitudinal study recruited 37 participants with no prior COVID‐19 exposure (eight people recruited prior to the COVID‐19 pandemic – labeled pre‐COVID, 16 vaccinated and 13 non‐vaccinated participants). An enzyme‐linked immunosorbent assay (ELISA) was used to determine antibody levels against S1‐RBD in saliva (n=90) and GCF (n=80) samples obtained at 1 and 3 weeks after dose 1, and 3 days, 7 days, and 3 weeks after dose 2. To determine previous SARS‐CoV‐2 infection status, anti‐nucleocapsid (N) Ig levels were determined in samples from the pre‐COVID (saliva as reference), non‐vaccinated (saliva and GCF), and vaccinated (saliva and GCF) participants at 1‐week post‐dose 1 using ELISA. Results: Salivary levels of anti‐N antibodies measured in samples from vaccinated and nonvaccinated participants were comparable to those in pre‐COVID saliva samples collected between October 2018 and September 2019, thus confirming that all study participants had no prior SARS‐CoV‐2 infection. Overall, the levels of anti‐S1‐RBD antibodies peaked at 3 weeks after dose 2 in both saliva and GCF for all three immunoglobulin isotypes. Notably, the concentration of anti‐S1‐RBD antibodies in GCF was significantly higher than in saliva at all time points. Conclusion: This study establishes GCF and saliva as viable alternative non‐invasive sources to monitor levels of antibodies following vaccination, with GCF demonstrating feasibility as a biofluid source for the detection of antibodies against SARS‐CoV‐2 S1‐RBD antigen.